PENGARUH BEBAN KERJA, KOMPETENSI, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PERINDUSTRIAN DAN TENAGA KERJA KABUPATEN - I Made Nova Wirawan; I Putu Bagus Suthanaya (Universitas Triatma Mulya, 2026)
This study aims to determine the effect of workload, competence, and work discipline on employee performance at the Badung Regency Industry and Manpower Office. The population in this study was all employees of the Badung Regency Industry and Manpower Office, with sampling using total sampling technique. Data collection was conducted by distributing questionnaires to 72 respondents, which were then analysed using multiple linear regression, t-tests, and beta efficiency. The results of the study show that, partially, the variables of workload and work discipline have a negative and significant effect on employee performance, while the variable of competence has a positive and significant effect on employee performance. This means that the more evenly the workload is distributed, the better the competency through the training provided, and the stricter the company's discipline, the better the employee performance will be. Simultaneously, the three variables with the highest beta coefficient are the competency variable with a value of 0.428. These findings are expected to be used as evaluation material for management in formulating strategic policies to improve employee performance.